Initiating electronic cigarettes business in indonesia: value, prospects, and challenges - Putra Mahardika, Ibnu Prabowo; Budi Nugroho, Anggoro (The Indonesian Journal of Business Administration, 2016)
Abstract - In a global scale, Personal Vaporizer industry is developing rapidly, especially in developed countries. The governments in those countries simply supporting the PV industries with not banned the circulation but still under supervision of local public health bureau. In Indonesia, Personal Vaporizer industry is still very young, and our government haven’t postured anything at all. Regarding the presence of the industry. One of many seller who’s trying to expand its business is VAPLE. Regardless its rapid growth, currently VAPLE is experiencing financial issues, due to decreasing amount of new customer. To alleviate the problem, currently VAPLE is attempting to find new investor to placed their money for VAPLE’s development and fix VAPLE’s financial issues. The outcome of the research through Financial and Business Valuation point of view, indicated that VAPLE have a good opportunity for investment to be flourished. This statement is supported by positive NPV and bigger value that the cost of capital, short payback period, outstanding Internal Rate of Return, and Profitability Index value higher than 1. In conclusion based on the indicators above, VAPLE is a promising business. The research generates a few recommendations to fix VAPLE’s financial issues. Seek for a new places to doing business is the top priority, while also simultaneously enter new online market place. Another recommendations is to restock new and fast moving items, and lastly is attending local and global vape exhibition to allow VAPLE’s cash flow back to normal. Keywords: Personal Vaporizer, Qualitative Method, Finance, Business Valuation